The species-area-energy relationship in orchids - Schödelbauerová, Iva (2015)
Area, energy available and latitude are the main factors influencing species richness: (1) species richness increases with area – the species-area relationship (SAR); (2) according to the species-energy rela- tionship (SER) the energy available to an assemblage (i.e. that which it can turn into biomass) at a particular spatial resolution influences the species richness; (3) there are more species per unit area in the tropics than in the temperate regions. To test the relative importance of area, energy available and latitude on species richness, we have collected data on species richness of orchids for various areas in the world and calculated the mean Normalized Difference Vegetation Index (NDVI) as a measure of energy availability in these areas. We show that area considered is always very important, and that latitude is more important than ener- gy available.